Sex Influence on Heart Failure Prognosis - Postigo, Andrea; Martínez-Sellés, Manuel (Frontiers in Cardiovascular Medicine, 2020)
Heart failure (HF) affects 1-2% of the population in developed countries and approximately 50% of patients living with it are women. Compared to men, women are more likely to be older and suffer hypertension, valvular heart disease, and non-ischemic cardiomyopathy. Since the number of women included in prospective HF studies has been low, much information regarding HF in women has been inferred from clinical trials observations in men and data obtained from registries. Several relevant sex-related differences in HF patients have been described, including biological mechanisms, age, etiology, precipitating factors, comorbidities, left ventricular ejection fraction, treatment effects, and prognosis. Women have greater clinical severity of HF, with more symptoms and worse functional class. However, females with HF have better prognosis compared to males. This survival advantage is particularly impressive given that women are less likely to receive guideline-proven therapies for HF than men. The reasons for this better prognosis are unknown but prior pregnancies may play a role, among others. In this review article we aim to describe sex-related differences in HF and how these differences might explain why women with HF can expect to survive longer than men.